1999
DOI: 10.1037/0022-006x.67.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Conscious and nonconscious African American stereotypes: Impact on first impression and diagnostic ratings by therapists.

Abstract: Sixty therapists randomly assigned to 1 of 2 priming conditions were primed with African American stereotypes or neutral words using 80-ms flash words on a computer screen. This procedure may activate information processing outside of conscious awareness. After this task, participants were exposed to a brief vignette introducing Mr. X, a patient referred for treatment, and then were asked to rate Mr. X on various dimensions. Results indicate that participants primed with stereotype words rated Mr. X significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 35 publications
5
101
1
1
Order By: Relevance
“…How people experience and report pain, for example, varies greatly and systematically with patient characteristics (Bonham, 2001). There have been many creative experiments, using vignettes (Weisse et al, 2001;Rathore et al, 2000), subliminal messages flashed on computer screens (Abreu, 1999), or observations of medical training (Finucane and Carrese, 1990) to study the presence of bias and stereotyping among medical professionals (bias and stereotypes are not distinguished in the studies just noted). What is missing in the literature, in our view, is the empirical connection between these phenomena and differential treatment of racial/ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…How people experience and report pain, for example, varies greatly and systematically with patient characteristics (Bonham, 2001). There have been many creative experiments, using vignettes (Weisse et al, 2001;Rathore et al, 2000), subliminal messages flashed on computer screens (Abreu, 1999), or observations of medical training (Finucane and Carrese, 1990) to study the presence of bias and stereotyping among medical professionals (bias and stereotypes are not distinguished in the studies just noted). What is missing in the literature, in our view, is the empirical connection between these phenomena and differential treatment of racial/ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…The stereotype exposure led to overestimations of hostility, and Abreu asserted that such implicit bias toward African Americans could influence clinical judgments of hostility. Abreu's (1999) valuable study should be updated and expanded. Specifically, implicit attitudes about several targets of bias should be measured using a sample of current counselor trainees.…”
Section: Implicit Measurement Of Biasmentioning
confidence: 99%
“…We hypothesized that counselor trainees would report high levels of MCC and that MCC would significantly vary by level of multicultural training. However, because of the divergence that is often found between implicitly and explicitly measured bias and the initial documentation of implicit bias among counselors by Abreu (1999), we hypothesized that counselor trainees would exhibit implicit bias, and that this bias would not vary by level of multicultural training.…”
Section: The Current Studymentioning
confidence: 99%
“…It hard to imagine a board-certified clinician making a decision about an African American patient (or a patient of any other ethnic group) with no conscious consideration of how the person's race (or gender, age or socioeconomic position) might influence the clinical encounter. In fact, one experimental study found partial evidence that clinicians consciously attempted to overcome the influence of racial stereotyping once a hypothetical clinical case was identified as black (Abreu 1999). Similarly, a recent experiment where video-taped symptom presentations were carefully matched across patient race found that psychiatrists did not under-diagnose depression among African Americans (Kales et al 2002).…”
Section: Clinician Biasmentioning
confidence: 99%
“…No doubt some clinicians possess negative attitudes and opinions about African Americans and it is very possible that such negative attitudes are responsible for over-pathologizing African American patients (van Ryn and Burke 2000). However, the research in this area is inconsistent and, as a result, it is not clear how such attitudes influence the psychiatric diagnostic process (Abreu 1999). It is clear, however, that due to the limited nature of the research on clinician bias, this topic is in dire need of additional study (U.S. Department of Health and Human Services 2001).…”
Section: Introductionmentioning
confidence: 99%